Probing an Interfacial Ionic Pairing‐Induced Molecular Dipole Effect in Ionovoltaic System. Issue 7 (6th June 2021) - Yoon, Sun Geun; Park, Byoung Joon; Jin, Huding; Lee, Won Hyung; Han, Junghyup; Cho, Yong Hyun; Yook, Hyunwoo; Han, Jeong Woo; Kim, Youn Sang
Abstract: A surficial molecular dipole effect depending on ion‐molecular interactions has been crucial issues regarding to an interfacial potential, which can modulate solid electronic and electrochemical systems. Their properties near the interfacial region can be dictated by specific interactions between surface and adsorbates, but understandings of the corresponding details remain at interesting issues. Here, intuitive observations of an ionic pair formation‐induced interfacial potential shifts are presented with an ionovoltaic system, and corresponding output signal variations are analyzed in terms of the surficial dipole changes on self‐assembled monolayer. With aiding of photoelectron spectroscopies and density function theory simulation, the ionic pair formation‐induced potential shifts are revealed to strongly rely on a paired molecular structure and a binding affinity of the paired ionic moieties. Chemical contributions to the binding event are interrogated in terms of polarizability in each ionic group and consistent with chaotropic/kosmotropic character of the ionic groups. Based on these findings, the ionovoltaic output changes are theoretically correlated with an adsorption isotherm reflecting the molecular dipole effect, thereby demonstrating as an efficient interfacial molecular probing method under electrolyte interfacing conditions. Abstract : Ionic pair formations and corresponding molecular dipole shifts are probed at the electrolyte/electrode interface via an ionovoltaic system. The paired molecule‐dependent output voltage transitions are correlated with interfacial dipole changes and binding affinities between paired ionic groups. The experimental results demonstrate the applicability of this system as an interfacial and molecular probing tool.